2006
DOI: 10.1152/physrev.00018.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sodium/Calcium Exchanger: Influence of Metabolic Regulation on Ion Carrier Interactions

Abstract: The Na+/Ca2+ exchanger's family of membrane transporters is widely distributed in cells and tissues of the animal kingdom and constitutes one of the most important mechanisms for extruding Ca2+ from the cell. Two basic properties characterize them. 1) Their activity is not predicted by thermodynamic parameters of classical electrogenic countertransporters (dependence on ionic gradients and membrane potential), but is markedly regulated by transported (Na+ and Ca2+) and nontransported ionic species (protons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
157
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 238 publications
4
157
0
4
Order By: Relevance
“…It is well known that anesthetics with different chemical and pharmacological profiles [31][32][33] significantly affect metabolic processes which play an important role in regulation of cell volume [12,34]. Therefore, in present experiments the animals were sharply immobilized by freezing method (dipping their noses into liquid nitrogen for 3-4 sec) and decapitated [35].…”
Section: Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that anesthetics with different chemical and pharmacological profiles [31][32][33] significantly affect metabolic processes which play an important role in regulation of cell volume [12,34]. Therefore, in present experiments the animals were sharply immobilized by freezing method (dipping their noses into liquid nitrogen for 3-4 sec) and decapitated [35].…”
Section: Tissue Preparationmentioning
confidence: 99%
“…It is known that Ca ions can be removed from cells by two mechanisms: Ca-pump and Na + /Ca 2+ exchange in forward mode. Notwithstanding the affinity of Ca-pump is higher than Na + /Ca 2+ exchange because the latter has incomparably higher rate than Ca-pump, it is suggested that Na + /Ca 2+ exchange has a more essential role in regulation of [Ca] i homeostasis [12,34]. There is a great number of literature data about the crucial role of α 3, α 2 isoforms of Na + /K + in regulation of Na + /Ca 2+ exchange.…”
Section: Camentioning
confidence: 99%
“…Se ha aceptado que la relajación de la fibra muscular esquelética es consecuencia de la activación de la SERCA del retículo sarcoplásmico y de la unión del Ca 2+ a la parvalbúmina. Sin embargo, en los últimos años se ha propuesto la participación de las mitocondrias y del intercambiador Na + -Ca 2+ en este proceso, ya que ambos se encuentran involucrados en la regulación de la homeostasis de Ca 2+ en otros tipos celulares, excitables y no excitables (157).…”
Section: Otras Preguntasunclassified
“…The NCX proteins are regulated by cytosolic Na ϩ and Ca 2ϩ (10 -13). A rise in Na ϩ rapidly stimulates and then inactivates the exchanger, whereas cytosolic Ca 2ϩ activates NCX1 and relieves the Na ϩ -dependent inactivation (11)(12)(13)(14)(15)(16). The alternative splicing of NCX1 dramatically alters the relationships between Na ϩ -dependent and Ca 2ϩ -dependent regulation (12)(13)(14).…”
mentioning
confidence: 99%